2020
DOI: 10.1177/1078155220941060
|View full text |Cite
|
Sign up to set email alerts
|

Risk reduction in a cancer chemotherapy production unit: Contribution of an automated drug dispensing system

Abstract: Objective The purpose of our study was to evaluate the contribution of an automated drug dispensing system in securing cancer chemotherapy production process at the pharmacy of the National Institute of Oncology in Rabat. Methods The failure modes and effects analysis method was applied to the chemotherapy production process in two phases: Phase 1, using an open shelf for storage then phase 2, using an automated drug dispensing system. The failure modes were defined and their criticality indexes was calculated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
3
0
1
Order By: Relevance
“…Lorely et al (Mila et al, 2010(Mila et al, , 2012 used a risk analysis methodology, failure mode effects analysis (FMEA), as a quality risk assessment and control tool for the vaccine production process to perform risk assessment of the entire production process of hepatitis B vaccine. Jean-Marie et al (Ouedraogo et al, 2021) also applied FMEA as a risk assessment tool for the production of cancer chemotherapy drugs and concluded that automated dispensing systems can minimize production risks. Laure et al (Pujol et al, 2013) combined quantitative microbial risk assessment techniques and risk management indicators to evaluate and control the high-temperature transient sterilization process in pharmaceutical production.…”
Section: Drug Production Risk Assessment Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lorely et al (Mila et al, 2010(Mila et al, , 2012 used a risk analysis methodology, failure mode effects analysis (FMEA), as a quality risk assessment and control tool for the vaccine production process to perform risk assessment of the entire production process of hepatitis B vaccine. Jean-Marie et al (Ouedraogo et al, 2021) also applied FMEA as a risk assessment tool for the production of cancer chemotherapy drugs and concluded that automated dispensing systems can minimize production risks. Laure et al (Pujol et al, 2013) combined quantitative microbial risk assessment techniques and risk management indicators to evaluate and control the high-temperature transient sterilization process in pharmaceutical production.…”
Section: Drug Production Risk Assessment Methodsmentioning
confidence: 99%
“…Failure mode effects analysis (Mila et al, 2010(Mila et al, , 2012Ouedraogo et al, 2021) The quantitative method has the advantage of higher accuracy compared to the qualitative method, but does not take into account the interaction between risk factors and is difficult to obtain data information…”
Section: Quantitative Methodsmentioning
confidence: 99%
“…Nombreux sont les établissements hospitaliers ayant augmenté le nombre d’APS au cours de la pandémie COVID-19 [22] . En plus de limiter les risques d’erreurs médicamenteuses et de réduire les coûts [23] , [24] , les APS permettent un suivi en ligne des consommations des services de soins. Un rapport d’activité est généré en fin de chaque journée de travail ouvrable au niveau de la PC, récapitulant les consommations de chaque service.…”
Section: Sécurisation Du Circuit Médicamenteux Et Suivi De L’état De ...unclassified
“…It has been proven effective many times for safety risk management in chemotherapy care. 18,20,21 Our group recently developed a CPOE software called ONCO-Expert that also fulfills the following purposes: collect patient data in real time, monitor the chemotherapy prescription and perform research activities. This software leverages assets from the platform we have been using for antimicrobial stewardship since 2010.…”
Section: Introductionmentioning
confidence: 99%